Modelling of water droplets heat and mass transfer in the course of phase transitions. II: Peculiarities of the droplet radial coordinate and the time grid calibration - Miliauskas, Gintautas; Adomavicius, Arvydas; Maziukienė, Monika (Nonlinear Analysis: Modelling and Control, 2017)
This paper continues optimization of numerical solution algorithm of iterative scheme grid for the droplet task, which was presented in the first article of this series. Assumptions were made by optimal assessable number of members which was already defined in numerical experiment in case of compound heat spread by conduction and radiation and an unsteady temperature field was described by infinite integral equation sum. For the convenience of numerical analysis, droplet thermal parameters PT were described by universal Fourier criteria Fo and by dimensionless radial coordinate η function PT(Fo,η). This function is given in form of infinite integral equation sum with each thermal parameter having a distinct initial member and individually defined subsidiary function. This function is given in form of infinite integral equation sum with each thermal parameter having a distinct initial member and individually defined subsidiary function. The droplet time and radial coordinate grading change influence for calculated function graphs PT(Fo,η) was evaluated by water droplets heat transfer and phase transformation numerical experiment. Summarizing by conduction and radiation heated water droplets thermal parameter variation patterns a methodology of forming an optimal grid for droplet task’ task iterative solving, is provided.